A mixed methods study of the awareness and management of familial hypercholesterolaemia in Irish general practice - Robyn Homeniuk; Joseph Gallagher; Claire Collins (Frontiers in Medicine, 2022)
IntroductionFamilial Hypercholesterolemia (FH) is one of the most common genetic disorders, with an estimated global prevalence of 1:200-500, which leads to premature cardiovascular disease. Nevertheless, public and professional awareness of FH is often lacking, with an estimated 20,000 largely undiagnosed cases in Ireland.PurposeThe overall aim of the project was to test the feasibility of a model of care that would include electronic record screening, clinical assessment, and coding of possible FH patients across a network of general practices in Ireland. In addition, a secondary aim was to gauge the awareness and knowledge of FH across the network.MethodsThis study took part in multiple phases, employing a mixed methods design. The study included a validated questionnaire, tailored online educational resources, a retrospective chart review of patients with a history of elevated LDL cholesterol (LDLc) and an active review with a selection of those patients. Results were analyzed using SPSS V27, where descriptive statistics and relevant correlation tests were employed.ResultsEighteen general practices agreed to take part in the study. In the initial survey, respondents rated their personal and practice familiarity with FH as slightly below average. Around one-third of respondents were not aware of FH guidelines. Of over 55,000 adult patient records searched, only 0.2% had a recorded FH diagnosis and 3.9% had ever had an LDLc above 4.9 mmol/l. Eight practices completed 198 chart reviews. Among these, 29.8% of patients had a family history recorded, and 22.2% had a family history of CVD recorded. Female patients had higher averages for highest and recent LDLc. Seventy patients underwent a clinical review—with 27% of these patients identified as “probable” or “definite FH.” There was a statistically significant (p = 0.002) relationship between FH status and whether the patient had other CVD risk factors.ConclusionGeneral practitioners in Ireland had similar levels of awareness of FH compared to findings from elsewhere. The activities discussed encouraged clinicians to consider FH when talking to their patients, especially those with elevated LDLc at an early age. Broader awareness of the condition could increase conversations about FH and benefit patient outcomes.